The effect of household and corporate loans on current account balance: Evidence from the Western Balkan countries - Egzona Hani Selimi; Milan Eliskovski (Journal of Contemporary Economic and Business Issues, 2019)
The economic literature indicates that the loans relative to GDP in the economy, are important factors that influence the current account movements in a country. Therefore, the purpose of this study is estimating and then quantifying the effects that household and corporate loans have on the current account balance in the Western Balkan countries (Albania, Bosnia and Herzegovina, Montenegro, North Macedonia, Serbia and Turkey). The expectations are that different kind of borrowers might vary in terms of the use of loans and thus might have different effects on macroeconomic variables. The results are obtained by estimating a Vector Error Correction Model (VECM), and they imply that household loans have negative effect on the current account balance, while there is evidence that corporate loans have positive effect for some countries (Bosnia and Herzegovina and North Macedonia) and negative effect on the external balance for the rest of the countries. The findings in this paper coincide with the ex-ante expectations, given the import pressures that household loans might induce and the positive/negative impact that corporate loans might have on the overall productivity and competitiveness of the economy.
Keywords: F32; F41; F14; E51; 330; Household loans; Corporate loans; Current account balance; Western Balkan countries